Preparation method and application of thermosetting resin-based binder for lithium battery

By mixed the thermosetry resin and polysaccharide biomass, to prepare low -cost, high tough lithium battery adhesives, the problem of high cost and insufficient toughness of the existing adhesives, and realizing the stability and stability of the battery. Reliability improvement.

CN119351011APending Publication Date: 2025-01-24DALIAN POLYTECHNIC UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411695256.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing lithium-ion battery binders are expensive and complex in preparation process, and insufficient toughness cannot meet the volume expansion needs of silicon-carbon negative electrodes.

Method used

The low-cost, easy-to-industrial thermosetting resin is blended and modified with polysaccharide biomass to improve the elasticity and tensile properties of the thermosetting resin and is used to prepare binders for lithium batteries.

Benefits of technology

The cost of the binder is reduced, the toughness and tensile properties of the binder are improved, the stability and reliability of the battery are ensured, and the problem of water absorption of the electrode sheet is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351011A_ABST
    Figure CN119351011A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a preparation method and application of a thermosetting resin-based binder for a lithium battery. The preparation method comprises the following steps: (1) uniformly mixing thermosetting resin and polysaccharide biomass; and (2) uniformly mixing the mixture obtained in the step (1) with a dispersing agent to obtain the thermosetting resin-based binder. The polysaccharide biomass and the thermosetting resin are blended to modify the thermosetting resin, so that the elasticity and plasticity of the thermosetting resin are improved, good tensile property is ensured, and high-valued utilization of the polysaccharide biomass is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a preparation method and application of a thermosetting resin-based binder for lithium batteries. Background Art

[0002] In today's society, energy issues are crucial in economic construction and social development. In this context, lithium-ion batteries have become very important as an energy storage solution. Lithium-ion batteries have the advantages of high energy density, long life, fast charging speed and lightweight, and are widely used in electronic products, electric vehicles, energy storage power stations, aerospace, medical equipment and military security. Lithium-ion batteries contain components such as positive electrodes, negative electrodes, electrolytes and separators. In the electrodes of lithium-ion batteries, binders are important components. They play the role of bonding active materials, conductive agents and current collectors, and have an important influence on maintaining the integrity of the electrodes and constructing the transmission channels of ions and electrons. Although the binder itself has no capacity and accounts for a small proportion in the battery, it is the main source of the mechanical properties of the entire electrode. Therefore, it is necessary to develop high-performance, electrolyte swelling and corrosion-resistant, low-cost binders.

[0003] At present, the main types of lithium-ion battery binders are: polyvinylidene fluoride (PVDF), styrene-butadiene rubber latex, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile and polyacrylate. PVDF is the first widely used lithium-ion battery binder with strong resistance to electrochemical corrosion. PVDF is a polymer fluoride material. Its production requires strictly controlled high temperature, high pressure and specific fluorine chemical reaction conditions. Lithium-grade PVDF is expensive, and PVDF binders are not tough enough to meet the volume expansion of silicon-carbon negative electrodes. Moreover, PVDF requires N-methylpyrrolidone (NMB), an expensive and highly toxic organic reagent, as a solvent, and has a strong dependence on solvents. In summary, there is an urgent need to develop low-cost, easy-to-industrialize and tough battery binders.

[0004] Thermosetting resins have good heat resistance, stability, chemical resistance and wear resistance, but they have some disadvantages when used in battery materials, such as being generally brittle after curing and having poor impact resistance. In battery applications, the stress generated by the volume change of electrode materials during charging and discharging may cause cracking of the bonding interface or powdering of the electrode. Summary of the invention

[0005] In order to reduce the high cost and complex preparation process of lithium battery binders, the present invention provides a preparation method and application of a thermosetting resin-based binder for lithium batteries. Low-cost and easily industrialized thermosetting resin is used as a raw material, and it is blended and modified with polysaccharide biomass. Polysaccharide biomass has good degradability, a wide range of sources, and good renewability. It is a new type of green and environmentally friendly material. Polysaccharide biomass is used for resin blending and modification, so that the thermosetting resin has elasticity and tensile properties. It is used in lithium battery binders to solve the problem of high cost of lithium battery binders and broaden the application prospects of resins in lithium battery binders.

[0006] To achieve the above technical objectives, the technical solution of the present invention is as follows:

[0007] One aspect of the present invention provides a method for preparing a thermosetting resin-based binder for a lithium battery, the method comprising the following steps:

[0008] (1) mixing the thermosetting resin and the polysaccharide biomass uniformly;

[0009] (2) The mixture obtained in step (1) is mixed evenly with a dispersant to obtain the thermosetting resin-based binder.

[0010] Preferably, the thermosetting resin is one of phenolic resin, lignin phenolic resin, epoxy resin, unsaturated polyester resin, amino resin, polyurethane resin and silicone resin.

[0011] Preferably, the polysaccharide biomass is one of starch, dextran, guar gum, chitosan, sodium alginate, cellulose, pectin, spiny bean gum, and fenugreek gum.

[0012] Preferably, the mass ratio of the thermosetting resin to the polysaccharide biomass is (10:1)-(1:10).

[0013] Preferably, the uniform mixing is performed by one or more of grinding, stirring and ball milling.

[0014] Preferably, the dispersant is one or more of water, ethanol, methanol and isopropanol.

[0015] Preferably, the solid content of the thermosetting resin-based binder is 5%-50%.

[0016] Another aspect of the present invention provides an electrode sheet, wherein the electrode sheet is obtained by coating a slurry containing an electrode active material, a conductive agent and a binder on a current collector.

[0017] When the electrode active material is a positive electrode active material, the electrode sheet is a positive electrode sheet; when the electrode active material is a negative electrode active material, the electrode sheet is a negative electrode sheet.

[0018] Preferably, the mass percentage of the binder in the electrode sheet is 0.5%-20%.

[0019] The present invention also provides a lithium ion battery, which comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet and / or the negative electrode sheet is the above-mentioned electrode sheet.

[0020] The beneficial effects of the present invention are:

[0021] The present invention improves the elasticity and plasticity of the thermosetting resin by blending polysaccharide biomass with thermosetting resin, ensures good tensile properties, and realizes the high-value utilization of polysaccharide biomass. At the same time, the low hydroxyl content of the thermosetting resin-based material avoids the water absorption problem of the electrode sheet, thereby preventing the decomposition of the electrolyte in the water during the battery cycle. The binder prepared by the present invention not only improves the binder performance, but also ensures the stability and reliability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The cycle efficiency diagram of the half-cell assembled with the negative electrode sheet prepared in Comparative Example 1;

[0023] Figure 2 The cycle efficiency diagram of the half-cell assembled with the negative electrode sheet prepared in Comparative Example 2;

[0024] Figure 3 This is a cycle efficiency diagram of a half-cell assembled with a positive electrode sheet prepared in Comparative Example 3;

[0025] Figure 4 The cycle efficiency diagram of the half-cell assembled with the positive electrode sheet prepared in Comparative Example 4;

[0026] Figure 5 The cycle efficiency diagram of the half-cell assembled with the negative electrode sheet prepared in Example 1;

[0027] Figure 6 The cycle efficiency diagram of the half-cell assembled with the negative electrode sheet prepared in Example 4;

[0028] Figure 7 This is a cycle efficiency diagram of a half-cell assembled with the positive electrode sheet prepared in Example 5;

[0029] Figure 8 This is a cycle efficiency diagram of a half-cell assembled with the positive electrode sheet prepared in Example 6;

[0030] Fig. 9 This is a cycle efficiency diagram of a half-cell assembled with the negative electrode sheet of Example 7;

[0031] Fig.10 The cycle efficiency diagram of the negative electrode sheet assembled half-cell of Example 8;

[0032] Fig.11 This is a cycle efficiency diagram of a half-cell assembled with the positive electrode sheet of Example 9;

[0033] Fig.12 This is a cycle efficiency diagram of a half-cell assembled with the positive electrode sheet of Example 10;

[0034] Fig.13 The tensile diagrams of the phenolic resin-guar gum films prepared in Examples 1-3 are compared. DETAILED DESCRIPTION

[0035] The present invention is described in detail below through specific examples. However, the present invention is not limited to the following examples, and the implementation conditions used in the examples can be further adjusted according to different requirements of specific use, and the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0036] Comparative Example 1

[0037] (1) Weigh 0.3 g of silicon-carbon alloy negative electrode material (Crode, Si-C950-K), 0.1 g of acetylene black, and 1 g of PVDF (Crode, PVDF 5130) in a mortar, mix well, and grind for 30 min;

[0038] (2) Add 9 g of solvent N-methylpyrrolidone to the mixture obtained in step (1) to obtain a negative electrode slurry, continue grinding until it is uniform, apply it on a copper foil using a 150 μm scraper, and vacuum dry it at 80° C. for 10 h to obtain a negative electrode sheet.

[0039] The half-cell was assembled in the order of negative electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and negative electrode sheet. The electrolyte used for the negative electrode was LX-025 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are shown in the figure. Figure 1 shown.

[0040] Comparative Example 2

[0041] Comparative Example 2 uses the same electrode preparation method and half-cell assembly method as Comparative Example 1, except that nano-silicon negative electrode material (Aladdin reagent, nano-silicon 99.99%) is used to prepare the negative electrode sheet, and the assembled half-cell is tested at a current density of 0.1C. The test results are as follows: Figure 2 shown.

[0042] Comparative Example 3

[0043] Comparative Example 3 uses the same electrode preparation method as Comparative Example 1, except that a lithium phosphate (LFP) positive electrode material (Crode, lithium iron phosphate (D-3)) is used to prepare the positive electrode sheet, and the half-cell is assembled in the order of positive electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and positive electrode sheet. The electrolyte used for the positive electrode is LX-014 (Duoduo Chemical Reagent). The assembled half-cell is tested at a current density of 0.1C, and the test results are as follows: Figure 3 shown.

[0044] Comparative Example 4

[0045] Comparative Example 4 uses the same electrode preparation method as Comparative Example 1, except that the positive electrode sheet is prepared using a ternary NCM positive electrode material (Crode, NCM622), and the half-cell is assembled in the order of positive electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and positive electrode sheet. The electrolyte used for the positive electrode is LX-014 (Duoduo Chemical Reagent). The assembled half-cell is tested at a current density of 0.1C, and the test results are as follows: Figure 4 shown.

[0046] Example 1

[0047] (1) directly mixing and stirring phenolic resin and guar gum in a mass ratio of 3:1, and grinding them uniformly for later use;

[0048] (2) uniformly mixing the mixed powder with water to obtain a phenolic resin-guar gum binder;

[0049] The phenolic resin-guar gum film was prepared by solution casting method and the tensile properties were tested. Fig.13 shown.

[0050] (3) Weigh 0.48g of silicon-carbon alloy negative electrode, 0.16g of acetylene black, and 0.16g of phenolic resin-guar gum binder, mix, grind for 30 minutes, slowly add deionized water dispersant and use grinding to stir until the slurry is slurried, continue grinding and mixing for 30 minutes, and after obtaining a uniform slurry, use a 150μm scraper to apply it on a copper foil, and vacuum dry it at 80°C for 10 hours to obtain a negative electrode sheet. Assemble the half-cell in the order of negative electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and negative electrode sheet. The electrolyte used for the negative electrode is LX-025 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are as follows. Figure 5 shown.

[0051] Example 2-3

[0052] The binders of Example 2 and Example 3 were prepared by the same method as Example 1, except that the ratio of phenolic resin to guar gum was 1:1 and 2:1 respectively.

[0053] The phenolic resin-guar gum film was prepared by solution casting method and the tensile properties were tested. Fig.13 shown.

[0054] Example 4

[0055] Example 4 uses the same electrode preparation method and half-cell assembly method as Example 1, except that nano-silicon negative electrode material (Aladdin reagent, nano-silicon 99.99%) is used to prepare the negative electrode sheet. The assembled half-cell is tested at a current density of 0.1C. The test results are as follows: Figure 6 shown.

[0056] Example 5

[0057] Example 5 uses the same electrode preparation method as Example 1, except that a lithium phosphate positive electrode material (Crode, lithium iron phosphate (D-3)) is used to prepare the positive electrode sheet, and the half-cell is assembled in the order of positive electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and positive electrode sheet. The electrolyte used for the positive electrode is LX-014 (Duoduo Chemical Reagent). The assembled half-cell is tested at a current density of 0.1C, and the test results are as follows: Figure 7 shown.

[0058] Example 6

[0059] Example 6 uses the same electrode preparation method as Example 1, except that the positive electrode sheet is prepared using a ternary NCM positive electrode material (Crode, NCM-622), and the half-cell is assembled in the order of positive electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and positive electrode sheet. The electrolyte used for the positive electrode is LX-014 (Duoduo Chemical Reagent). The assembled half-cell is tested at a current density of 0.1C, and the test results are as follows: Figure 8 shown.

[0060] Example 7

[0061] (1) mixing epoxy resin and starch in a mass ratio of 5:1, and grinding them evenly for later use;

[0062] (2) uniformly mixing the mixed powder with ethanol to obtain an epoxy resin-starch adhesive;

[0063] (3) Weigh 0.48 g of silicon-carbon alloy negative electrode material (Croode, Si-C950-K), 0.16 g of acetylene black, and 0.16 g of epoxy resin-starch binder, mix, stir for 30 min, add solvent ethanol, continue stirring and mixing for 30 min, and use a 150-μm scraper to apply it on a copper foil after obtaining a uniform slurry. Vacuum dry it at 80°C for 10 h to obtain a negative electrode sheet.

[0064] The half-cell was assembled in the order of negative electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and silicon-carbon negative electrode sheet. The electrolyte used for the negative electrode was LX-025 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are shown in Fig. 9 shown.

[0065] Example 8

[0066] (1) Mixing unsaturated polyester resin and dextran in a mass ratio of 5:1, and grinding them uniformly for later use;

[0067] (2) mixing the mixed powder with deionized water to obtain an unsaturated polyester resin-dextran binder;

[0068] (3) Weigh 0.48 g of nano-silicon negative electrode material (Aladdin reagent, nano-silicon 99.99%), 0.16 g of acetylene black, and 0.16 g of unsaturated polyester resin-dextran binder, mix with other dry powders, grind for 30 min, add deionized water as solvent, continue grinding and mixing for 30 min, and after obtaining a uniform slurry, use a 150 μm scraper to apply it on a copper foil, and vacuum dry at 80°C for 10 h to obtain a negative electrode sheet.

[0069] The half-cell was assembled in the order of negative electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and silicon-carbon negative electrode sheet. The electrolyte used for the negative electrode was LX-025 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are shown in Fig.10 shown.

[0070] Example 9

[0071] (1) mixing polyurethane resin and chitosan in a mass ratio of 5:1 and ball milling them, and then mixing them evenly for later use;

[0072] (2) uniformly mixing the mixed powder with methanol to obtain a polyurethane resin-chitosan binder;

[0073] (3) Weigh 0.48 g of LFP positive electrode material (Croode, lithium iron phosphate (D-3)), 0.16 g of acetylene black, and 0.16 g of polyurethane resin-chitosan binder, mix, and ball mill for 30 min. Then add the solvent methanol and continue ball milling for 30 min. After obtaining a uniform slurry, use a 150-μm scraper to coat it on a copper foil and vacuum dry it at 80°C for 10 h to obtain a positive electrode sheet.

[0074] The half-cell was assembled in the order of positive electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and positive electrode sheet. The electrolyte used for the positive electrode was LX-014 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are shown in the figure. Fig.11 shown.

[0075] Example 10

[0076] (1) Mix silicone resin and pectin in a mass ratio of 5:1, and grind them evenly for later use;

[0077] (2) mixing the mixed powder and deionized water uniformly to obtain a silicone resin-pectin adhesive;

[0078] (3) Weigh 0.48 g of ternary NCM positive electrode material (Croode, NCM-622), 0.16 g of acetylene black, and 0.16 g of silicone resin-pectin binder, mix, grind for 30 min, add solvent deionized water, continue grinding and mixing for 30 min, and use a 150-micron scraper to coat the slurry on a copper foil and vacuum dry at 80°C for 10 h to obtain a positive electrode sheet.

[0079] The half-cell was assembled in the order of positive electrode shell, spring, gasket, lithium sheet (diameter 16mm), 3501 diaphragm (Crode), and positive electrode sheet. The electrolyte used for the positive electrode was LX-014 (Duoduo Chemical Reagent). The assembled half-cell was tested at a current density of 0.1C. The test results are shown in the figure. Fig.12 shown.

[0080] like Figure 5 As shown, the silicon-carbon negative electrode sheet prepared in Example 1 has a capacity retention rate of more than 80% after 300 cycles, and the capacity is maintained at 800 mAh g -1 , the first effect is 86%. Figure 6 As shown, the nano-silicon negative electrode prepared in Example 4 has a capacity retention rate of more than 80% after 300 cycles, and the capacity is maintained at 2300 mAh g -1 , the first effect is 78%. Figure 7 As shown in the figure, the lithium iron phosphate positive electrode prepared in Example 5 was cycled 300 times and the capacity was maintained at 150 mAh g -1 , the capacity retention rate is greater than 80%, and the first efficiency is 96%. Figure 8 As shown, the ternary NCM positive electrode prepared in Example 6 has a capacity retention rate of more than 80% after 300 cycles, and the capacity is maintained at 200 mAh g -1 About, the first effect is 84%.

[0081] By comparing Comparative Examples 1-4 with Examples 1 and 4-6, the performance of the pole pieces prepared in Examples 1 and 4-6 is significantly better than that in the comparative examples. Figure 1 As shown, the silicon-carbon negative electrode prepared in Comparative Example 1 has a capacity retention rate of 71% after 300 cycles, and the capacity is maintained at 693 mAh g -1 , the first effect is 66%, such as Figure 2 As shown, the nano-silicon negative electrode prepared in Comparative Example 2 has a capacity retention rate of 52% after 300 cycles, and the capacity is maintained at 2124 mAh g -1 , the first effect is 66%. Figure 3 As shown, the lithium iron phosphate positive electrode prepared in Comparative Example 3 has a capacity retention rate of 94% after 300 cycles, and the capacity is maintained at 135 mAh g -1 , the first effect is 70%. Figure 4 As shown, the NCM positive electrode prepared in Comparative Example 4 has a capacity retention rate of 69% after 300 cycles, and the capacity is maintained at 144 mAh g -1 , the first efficacy is 73%.

[0082] like Figure 9-12 As shown, Fig. 9 As shown, the silicon-carbon alloy negative electrode sheet prepared in Example 7 was cycled 300 times with a capacity retention rate of 74% and a capacity of 535 mAh g -1 , the first effect is 77%. Fig.10 As shown, the nano-silicon negative electrode prepared in Example 8 was cycled 300 times, with a capacity retention rate of 51% and a capacity of 1936 mAh g -1 , the first effect is 83%. Fig.11 As shown, the lithium iron phosphate positive electrode prepared in Example 9 was cycled 300 times, with a capacity retention rate of 83% and a capacity of 147 mAh g -1 , the first effect is 91%. Fig.12 As shown, the ternary NCM positive electrode prepared in Example 10 has a capacity retention rate of 84% after 300 cycles, and the capacity is maintained at 222 mAh g -1 , the first efficacy is 81%.

[0083] like Fig.13 As shown, the tensile properties of the phenolic resin-guar gum films prepared in Examples 1-3 were tested, and the elongation at break was 32% for 1:1, 60% for 2:1, and 81% for 3:1. Compared with phenolic resin, the elasticity and tensile properties were significantly improved.

[0084] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A method for preparing a thermosetting resin-based binder for lithium batteries, characterized in that: The method comprises the following steps: (1) mixing the thermosetting resin and the polysaccharide biomass uniformly; (2) The mixture obtained in step (1) is mixed evenly with a dispersant to obtain the thermosetting resin-based binder.

2. The preparation method according to claim 1, characterized in that: The thermosetting resin is one of phenolic resin, lignin phenolic resin, epoxy resin, unsaturated polyester resin, amino resin, polyurethane resin and silicone resin.

3. The preparation method according to claim 1, characterized in that: The polysaccharide biomass is one of starch, dextran, guar gum, chitosan, sodium alginate, cellulose, pectin, spiny bean gum and fenugreek gum.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the thermosetting resin to the polysaccharide biomass is (10:1)-(1:10).

5. The preparation method according to claim 1, characterized in that: The uniform mixing is performed by one or more of grinding, stirring and ball milling.

6. The preparation method according to claim 1, characterized in that: The dispersant is one or more of water, ethanol, methanol and isopropanol.

7. The preparation method according to claim 1, characterized in that: The solid content of the thermosetting resin-based binder is 5%-50%.

8. An electrode sheet, which is obtained by coating a slurry containing an electrode active material, a conductive agent and a binder on a current collector, characterized in that: The binder is prepared by the preparation method according to any one of claims 1 to 7.

9. The electrode sheet according to claim 8, characterized in that: The mass percentage of the binder in the electrode sheet is 0.5%-20%.

10. A lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein: The positive electrode sheet and / or the negative electrode sheet is the electrode sheet according to any one of claims 8 to 9.